Solution pattern for machine-to-cloud integration in medical robotics - Yee, Jingye; Yee Low, Cheng; Quan Chong, Zhen; Shien Soh, Wei; bin Abd Rahman, Ramhuzaini; Akhtar Hanapiah, Fazah; Ayuni Che Zakaria, Noor; Asmar, Laban; Rabe, Martin (International Journal of Engineering and Technology, 2019)
Industrial Revolution 4.0 is bringing a paradigm shift into the industrial world and also indirectly revolutionising the healthcare domain. The Internet of Things (IoT) brings a revolution in the healthcare industry and medical education. One of the vital developments involves integration of medical devices and robots with cloud through the internet. This paper thus describes a general solution guideline for developing the IoT compliant medical robots. For that, an upper limb part-task trainer for upper limb spasticity evaluation training for rehabilitation named BITA is used to demonstrate how cloud integration could be achieved at its system-level design.Â Â Â